2011
DOI: 10.1523/jneurosci.6181-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Controls Cone Opsin Expression in the Retina of Adult Rodents

Abstract: Mammalian retinas display an astonishing diversity in the spatial arrangement of their spectral cone photoreceptors, probably in adaptation to different visual environments. Opsin expression patterns like the dorsoventral gradients of short-wave-sensitive (S) and middle-to long-wave-sensitive (M) cone opsin found in many species are established early in development and thought to be stable thereafter throughout life. In mouse early development, thyroid hormone (TH), through its receptor TR␤2, is an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 42 publications
5
106
1
Order By: Relevance
“…Thus, our data suggest opsin switching as the cellular mechanism behind the double cone phenotypic plasticity observed. In the retinas of salmonid fishes and rodents, cell labelling studies with proliferation and differentiation markers have shown that cone production in the main (nonperipheral) retina is absent after development (Julian et al, 1998;Candal et al, 2005;Cheng et al, 2009;Glaschke et al, 2011). Our histological analyses further indicated that cone density and morphology did not change following transplantations.…”
Section: Phenotypic Plasticity In Opsin Expression: Cellular Origin Amentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, our data suggest opsin switching as the cellular mechanism behind the double cone phenotypic plasticity observed. In the retinas of salmonid fishes and rodents, cell labelling studies with proliferation and differentiation markers have shown that cone production in the main (nonperipheral) retina is absent after development (Julian et al, 1998;Candal et al, 2005;Cheng et al, 2009;Glaschke et al, 2011). Our histological analyses further indicated that cone density and morphology did not change following transplantations.…”
Section: Phenotypic Plasticity In Opsin Expression: Cellular Origin Amentioning
confidence: 54%
“…It thus seems that the reported phenotypic plasticity in opsin expression of fishes is probably based on changes in the relative numbers of spectral cone types. Such alterations in cell numbers can arise via the production and/or pruning of photoreceptors, as occurs in several species (Cornish et al, 2004;Cheng et al, 2006;Hoke et al, 2006;Chen et al, 2008;Hu et al, 2011), or as a switch in the opsin expressed within individual photoreceptors, as has been demonstrated in the rods of the European eel (Wood and Partridge, 1993) and in the cones of salmonid fishes and rodents (Szél et al, 1994;Cheng et al, 2006, Cheng andGlaschke et al, 2011). The importance of opsin phenotypic plasticity in colour sensitivity, and visual function in general, would then depend on the number and types of cones affected and their retinal distributions.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated whether altered neuroendocrine function in Dnmt1 fl/fl :Rx-Cre/+ mice might contribute to the striking difference in M-cones and almost complete absence of S-opsin-expressing cones, as cone opsin expression is controlled by thyroid hormone in developing and mature retina (Roberts et al, 2006;Glaschke et al, 2011). We examined the cones in adult hypopituitary Ames dwarf (Prop1 df/df ) mice.…”
Section: All Cell Types Except S-cones Are Present In Dnmt1 Mutant Rementioning
confidence: 99%
“…Mouse and rat cones can express two opsins, the short wavelength-sensitive S opsin and the medium/long-wavelength sensitive M opsin, and, as such, can be classified as S cones and M cones, respectively. In rats, the retinal cone mosaic consists of 10% S cones and 90% M cones Glaschke et al, 2011). In mice, however, the pattern is more complex (Fig.…”
Section: Establishing Opsin Expression Patterns In the Mouse Retinamentioning
confidence: 99%
“…Pharmacological suppression of its ligand thyroid hormone (TH) in adult mice leads to activation of S opsin and a concomitant reduction of M opsin in all cones (Glaschke et al, 2011). Similarly, this treatment also induces the expression of S opsin in M cones in rats, which usually do not exhibit coexpression (see above).…”
Section: Maintaining Photoreceptor Identity In the Mouse Retinamentioning
confidence: 99%